Equating With Miditests Using IRT. Issue 2 (May 2016) - Fitzpatrick, Joseph; Skorupski, William P.
Abstract : The equating performance of two internal anchor test structures—miditests and minitests—is studied for four IRT equating methods using simulated data. Originally proposed by Sinharay and Holland, miditests are anchors that have the same mean difficulty as the overall test but less variance in item difficulties. Four popular IRT equating methods were tested, and both the means and SDs of the true ability of the group to be equated were varied. We evaluate equating accuracy marginally and conditional on true ability. Our results suggest miditests perform about as well as traditional minitests for most conditions. Findings are discussed in terms of comparability to the typical minitest design and the trade‐off between accuracy and flexibility in test construction.